Prove that sec(theta)+csc(theta)=(sin(theta)+cos(theta))(tan(theta)+cot(theta))

mattgondek4 2021-01-07 Answered
Prove that sec(θ)+csc(θ)=(sin(θ)+cos(θ))(tan(θ)+cot(θ))
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

SchepperJ
Answered 2021-01-08 Author has 96 answers
RHS =(sin(t)+cos(t))(tan(t)+cot(t))=(sin(t)+cos(t))(sin(t)cos(t)+cos(t)sin(t))=(sin(t)+cos(t))sin2(t)+cos2(t)(sin(t).cos(t))
RHS =(sin(t)+cos(t))1(sin(t).cos(t))=(1cos(t)+1sin(t))=sec(t)+csc(t)= LHS
RHS = LHS
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more